The politics of climate change: domestic and international responses to a global challenge - Tosun, Jale; Peters, B. Guy (International political science review, 2021)
The contributions to this special issue examine the politics of domestic and international climate policy, concentrating on the role of institutions, interests, ideas, and networks. The outcomes of the policymaking processes are assessed with regard to their proportionality, that is, the balance between the benefits and costs of a policy. The contributions show that climate politics can lead to policy under- and overreactions. This introduction sets out the common research interest of the special issue and explains how the individual contributions relate to each other. To this end, it begins by providing the rationale for adopting the analytical perspective of comparative politics. Then it presents the conceptual framework and gives an overview of the contributions to this issue. Subsequently, it develops a research agenda that highlights avenues for future research and offers a brief conclusion that reflects on the potential of the concept of (dis)proportionality to advance the cumulative knowledge on climate politics and policies.